Safety assessment of Osilodrostat: The adverse event analysis based on FAERS database by means of disproportionality analysis - Lijun Li; Wanchen Zhao (PLoS ONE, 2025)
Background Osilodrostat is a medication recently approved for the treatment of Cushing’s syndrome. However, there is a current dearth of large-scale studies on the adverse events associated with Osilodrostat. Consequently, this study aims to comprehensively evaluate these adverse events using data from the FDA Adverse Event Reporting System (FAERS). Methods A disproportionality analysis was utilized to identify signals of adverse events linked to Osilodrostat. Furthermore, a Weibull distribution analysis was conducted to evaluate the temporal evolution of adverse events, and subgroup analyses were performed. The Wilcoxon test was applied to investigate differences in the temporal patterns of adverse events across different genders. Results A total of 1,078 cases related to Osilodrostat were identified, including 3,744 adverse events. The most frequent and severe signals of adverse events were investigations, off-label use, fatigue, nausea, and adrenal insufficiency. The median time to onset of adverse events related to Osilodrostat was 52 days after starting the medication. There was a gender difference in the median time to onset of adverse events, with a median of 15 days for males and 34 days for females. Conclusion This study provides a comprehensive evaluation of adverse events related to Osilodrostat, confirming some known side effects and revealing other potential risks. This information offers valuable insights for the clinical application of Osilodrostat.